2018
DOI: 10.1016/j.neuron.2017.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Clptm1 Limits Forward Trafficking of GABAA Receptors to Scale Inhibitory Synaptic Strength

Abstract: SUMMARY In contrast with numerous studies of glutamate receptor-associated proteins and their involvement in the modulation of excitatory synapses, much less is known about mechanisms controlling postsynaptic GABAA receptor (GABAAR) numbers. Using tandem affinity purification from tagged GABAAR γ2 subunit transgenic mice and proteomic analysis, we isolated several GABAAR-associated proteins including Cleft lip and palate transmembrane protein 1 (Clptm1). Clptm1 interacted with all GABAAR subunits tested and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 66 publications
1
81
0
Order By: Relevance
“…This work revealed shifts toward γ 2-GABA A R association with new protein pathway networks associated with cell surface adhesion, intracellular junctions, synaptic plasticity, endocytosis & recycling and ubiquitination ( Figure 6, Table 3), confirming similar fluctuations in membrane and intracellular trafficking occur in vivo and in vitro after DZP. Recent inhibitory synapse proteomics studies have identified a number of new protein synaptic constituents or modulators of GABA A R function (Butko et al, 2013;Kang et al, 2014;Nakamura et al, 2016b;Uezu et al, 2016;Ge et al, 2018). We show here that proteins known to have roles in synaptic function and trafficking of membrane receptors show changes in their association with γ 2-receptors.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This work revealed shifts toward γ 2-GABA A R association with new protein pathway networks associated with cell surface adhesion, intracellular junctions, synaptic plasticity, endocytosis & recycling and ubiquitination ( Figure 6, Table 3), confirming similar fluctuations in membrane and intracellular trafficking occur in vivo and in vitro after DZP. Recent inhibitory synapse proteomics studies have identified a number of new protein synaptic constituents or modulators of GABA A R function (Butko et al, 2013;Kang et al, 2014;Nakamura et al, 2016b;Uezu et al, 2016;Ge et al, 2018). We show here that proteins known to have roles in synaptic function and trafficking of membrane receptors show changes in their association with γ 2-receptors.…”
Section: Discussionmentioning
confidence: 60%
“…6, Table 3), confirming similar fluctuations in membrane and intracellular trafficking occur in vivo and in vitro after DZP. Recent inhibitory synapse proteomics studies have identified a number of new protein synaptic constituents or modulators of GABA A R function (66)(67)(68)(69)(70). We show here that proteins known to have roles in synaptic function and trafficking of membrane receptors show changes in their association with γ2-receptors.…”
Section: Discussionmentioning
confidence: 60%
“…They play an essential role in the nervous system and include γaminobutyric acid type A receptors (GABA A Rs), nicotinic acetylcholine receptors (nAChRs), 5-hydroxytryptamine type-3 receptors (5HT 3 Rs), and glycine receptors (GlyRs) [14]. To reach their final destination, individual subunits undergo synthesis, folding and assembly into pentameric receptors in the ER and then go through the ER-to-Golgi transport, post Golgi transport and surface membrane insertion [15][16][17][18][19][20]. Disturbing any biogenesis step of these neuroreceptors could influence their surface expression level and the functional synaptic transmission, and impairment of the neurotransmission process can lead to related neurological diseases [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the pHluorin/Myc‐tagged GABA A R pulldown experiment that identified 149 putative GABA A R interactors, IQSEC3 ranked in the middle of the protein list in terms of peptide count 25 . However, IQSEC3 was not identified in a recent GABA A R γ2‐subunit pull down study 5 . Nonetheless, IQSEC3 is clearly involved in the organization of GABAergic synapses, in particular, the correct alignment of the GABAergic pre‐ and postsynaptic compartments 23 .…”
Section: Discussionmentioning
confidence: 56%
“…It consists of multiple GlyRs, each composed of a pentamer of α1 and β subunits clustered by the synaptic scaffolding protein gephyrin (GPHN), and is thought to have limited ability for plastic change 3 . Recent interaction proteomics studies on ligand‐gated ion channels and membrane receptors, such as GABA A and glutamate receptors, have revealed the presence of many protein interactors 4–8 . However, the relatively simple composition known of the GlyR complex (GlyR α1β‐GPHN) may in part be explained by the low sensitive biochemical methods used in the previous studies, leaving additional interactors undetected.…”
Section: Introductionmentioning
confidence: 99%